Indonesia's Leadership in the Formation of ASEAN Identity - John Daniel Chrisvaldo Siahaan (CV. AFDIFAL MAJU BERKAH, 2026)
The discourse on ASEAN identity has recently come under renewed scrutiny amid the Association's efforts to play a more active role in shaping the regional architecture of the Indo-Pacific region, particularly through the ASEAN Outlook on the Indo-Pacific (AOIP). Having previously established a strong reputation as the driving force of regionalism in East Asia and the broader Asia-Pacific, thereby giving rise to the concept of ASEAN Centrality, ASEAN's relevance is now being questioned once again in the context of renewed great-power competition between the United States and the People's Republic of China. A key concern in this regard is the internal coherence of ASEAN itself. Lacking a centralized institution endowed with authoritative executive powers, ASEAN traditionally relies on its member states to take proactive roles in initiating proposals and achieving consensus through consultative processes (musyawarah). In this context, Indonesia has emerged as a country striving to fulfill such a leadership role. Often described as a natural leader within ASEAN, owing to its significantly larger territory and population compared to other Southeast Asian nations, Indonesia has actively promoted ASEAN's role in realizing the shared aspirations of peace and regional integration in Southeast Asia. The findings of this article demonstrate that Indonesia currently satisfies several key criteria for regional leadership and effectively performs various regional leadership functions within ASEAN. These efforts have produced a series of initiatives that foster closer relations among ASEAN member states and, indirectly, contribute to the perception of a collective ASEAN identity.